PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ISPRING SUITE UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN PPKn di SMK N 1 KALIWUNGU - Alvina Kurniawati; Nani Mediatati; Dionisius Heckie Puspoko Jati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out whether the development of Ispring Suite-based interactive learning media can increase students' interest in learning in Civics learning subjects at SMK N 1 Kaliwungu. This type of research uses Research and Development (R&D) development with the ADDIE development model. The research results showed that the learning media developed was declared suitable for use with material expert validation test results of 90% and media expert validation test results of 83%. The results of the analysis of data on learning interest of class After using the media, there were 4 students (16%) in the moderate category, 12 students (48%) in the high category and 9 students (36%) in the very high category. There is no longer any interest in learning from students in the low category.